Abordaje educativo de la sexualidad en estudiantes con discapacidad intelectual en una institución de educación secundaria costarricense - Badilla Fallas, Laura; Carvajal Pérez, Lucía; García Brenes, Viodelys; Solís Segura, Diana; Ugalde Valverde, Tatiana; Zamora Bolaños, Katherine; Solórzano Salas, Julieta (Universidad de Costa Rica, 2018)
This scientific article explains the results of a research work, by making the educational approach with by the professors in the III Cycle and Diversified Cycle of the Liceo San Miguel, of Desamparados, Costa Rica. It was considered the imperative need that the population with intellectual disabilities to receive sexual and affectionate education as a part of their human rights. The construction of reality was done from a qualitative and phenomenologic perspective; the participants were 10 teachers who worked on this topic in the years 2012 - 2017. The techniques to produce information were comprehensive interviews and the revision of planning documents and notebooks. Two categories of interest were defined: curricular aspect considered in the planning and the educational approach of the professors in these topics. The main results of the research are that the professors choose the contents to be taught according to their own personal judgment, and they use different educational techniques and resources they prepare; but they do not consult the national proposal for this specific topic. The educational strategies must adjust to the functional diversity of each student. The teachers believe it is evident the student population is interested and needs to receive sexual and affectionate education, in spite of the resistance of their families and teachers. This research becomes a reference for the teaching training institutions, and its main limitation was taking into consideration only the phenomenologic views of the professors.